Nonlinear modeling of compliant mechanism - Khan, Md. Raisuddin; Billah, Masum; Watanabe, Mitsuru (2013)
In this paper, feasibility of using pseudo-rigid-body modeling technique in examined on a simple modular compliant mechanism. A mathematical model is constructed to determine the non-linear behavior of large-deflections. The problem is solved using an iterative method. The solution to the non-linear model is then compared to empirical results collected from a mock-up of the compliant device. The pseudo-rigid-body model is then combined with a linear model to develop the complete solution, which shows behavior fairly close to the actual behavior of the mock-up.